Scrubs contamination, domestic laundry effect and workwear habits of clinical staff at a referral hospital. (19th February 2020) - Kokkinos, P.; Morgan, L.; Hughes, K.; Pollard, D.; Gasson, J.; Bowlt‐Blacklock, K.
Abstract : Objective: To determine contamination rates of scrub suits worn by veterinary surgeons and nurses following a single shift. Materials and Methods: Cross‐sectional preliminary study at a UK small animal referral centre. Sterilised scrub suits were distributed to veterinary surgeons (n = 9) and nurses (n = 9) at the beginning of their clinical shift and worn for at least 8 hours. They were then analysed for bacterial contamination before and after home laundry at 30°C. A questionnaire was distributed to hospital clinical staff regarding workwear habits. Results: Median bacterial counts were 47 (interquartile range: 14 to 162) and 7 (interquartile range: 0 to 27) colony forming units per cm 2 before and after laundering scrub suits. Bacteria identified included Staphylococcus sp., Enterococcus sp., Escherichia coli, Bacillus sp., Pseudomonas aeruginosa, Micrococcus sp., β‐haemolytic Streptococci and a Group G Streptococcus. From 101 staff surveyed, 64.0% reported wearing fresh, clean scrub tops and 58.4% fresh, clean trousers each day, while 64.4% left the workplace wearing the same clothing in which they undertook clinical work. Clinical Significance: Workwear contamination risks spread of pathogens into the community and personnel compliance with workplace guidelines warrants further attention. Home laundry at 30°C significantly decreases, but does not eliminate, the bacterial burden after a single shift.